PROJECT SCHOOLS AS A SCHOOL-BASED MANAGEMENT MODEL - Mert Baştaş; Ahmet Koc (Informascope, 2019)
Education is a very expensive investment with high opportunity costs. Efforts for attaining schools with intended quality top the agenda of world nations' education plans and programs. Turkish Ministry of National Education has also made several reforms to increase the quality of education. The latest reform made in the field of educational management model has been the project schools developed with various innovations. Including school principals into the teachers' selection process can be regarded as the new aspect of school-based management. Sharing authority to choose teachers with school principals is a brand new approach for the Turkish National Education system. This study aims to detect reflections of project schools' structural and managerial features in practice and depends on the qualitative method, including observation and interviewing techniques. The research sample comprises 15 Imam Hatip High Schools located in Istanbul in 2018-2019 Education Year and 23 teachers working in these schools. "Semi-structured Interview Questionnaire" was utilized for scaling. According to research results, we conclude that teachers in project schools are satisfied with the new education model. There seems to be a total increase in teachers' efficiency in addition to higher teacher performances, due to the teams built under the leadership of school principals.   Keywords: Project School, School-Based Management, Leadership, Teamwork